Effect of HELLP syndrome on acute kidney injury in pregnancy and pregnancy outcomes: a systematic review and meta-analysis - Qiang Liu; Guan-jun Ling; Shao-quan Zhang; Wen-qing Zhai; Yi-juan Chen (BMC, 2020)
Abstract Background HELLP syndrome may increase adverse pregnancy outcomes, though the incidence of it is not high. At present, the impact of HELLP syndrome on P-AKI (acute kidney injury during pregnancy) and maternal and infant outcomes is controversial. Thus, we conducted a meta-analysis to find out more about the relationship between HELLP syndrome and P-AKI and pregnancy outcomes. Methods We systematically searched PubMed, Embassy and Cochrane Databases for cohort studies and RCT to assess the effect of HELLP syndrome on P-AKI and maternal and infant outcomes. Study-specific risk estimates were combined by using fixed-effect or random-effect models. Results This meta-analysis included 11 cohort studies with a total of 6333 Participants, including 355 cases of pregnant women with HELLP syndrome and 5979 cases that without. HELLP syndrome was associated with relatively higher risk of P-AKI (OR4.87 95% CI 3.31 ~ 7.17, P<0.001), fetal mortality (OR1.56 95% CI 1.45 ~ 2.11, P<0.001) and Maternal death (OR3.70 95% CI 1.72 ~ 7.99, P<0.001). Conclusions HELLP syndrome is associated with relatively higher risk of P-AKI, fetal mortality and maternal death.